Manajemen Kurikulum dan Pembelajaran di Sekolah Menengah Atas - Sapitri, Riris (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to determine and describe the planning, organization, implementation, and evaluation of curriculum and learning at SMA Muhammadiyah 4 Yogyakarta. This research used a descriptive qualitative method. The research subjects consisted of the Vice Principal of Curriculum and Teachers. Data were collected through observation, interview, and documentation. Data analysis techniques were done through data reduction, data presentation, and conclusion drawing. The results showed that curriculum and learning management includes 1) Curriculum planning follows the national curriculum structure which refers to the rules of the Yogyakarta City Youth Education and Sports Office and the Yogyakarta City Secondary Education Office, as well as the preparation of the Al-Islam, Kemuhammadiyan, and Arabic Language (ISMUBA) Curriculum structure by the provisions of the Muhammadiyah Regional Leadership. 2) Organisation is carried out by a curriculum development team consisting of the school principal, curriculum vice-secretary, teachers, education personnel, and counseling guidance. 3) Implementation of the curriculum is integrated with the process of teaching and learning activities and making lesson schedules. 4) The Merdeka Curriculum evaluation includes formative and summative assessments, while the 2013 Curriculum assessment includes cognitive, affective, and psychomotor assessments. Curriculum and learning management at SMA Muhammadiyah 4 Yogyakarta has been running well by the objectives set